Sharia Capital Market Product Development Model In Moving The Real Sector Based on MSMEs In Indonesia - Robist Hidayat (Universitas Teuku Umar, 2021)
Micro, small and medium enterprises (MSMEs) were the pillars of the Indonesian economy when the crisis occurred in 1998. However, after the crisis, when economic conditions returned to normal, MSMEs encountered several obstacles in carrying out their activities. One of the problems faced by SMEs is a lack of capital. MSMEs do not meet the requirements to make loans to banks because they are considered unbankable. This limited capital is counterproductive because it can hamper the growth of MSMEs in Indonesia. MSMEs can overcome capital problems by utilizing investment instruments in the capital market, namely stocks and bonds. However, the use of the capital market as an alternative to MSME financing is still very minimal. From 1997 to 2011, only 9 MSMEs conducted IPOs or initial public offerings (Bapepam-LK, 2011:3). MSMEs need a third party both to issue and guarantee stocks and bonds. However, the government, which is expected to have a major role in supporting the real sector, has not played a role in encouraging MSMEs to enter the capital market. The government can provide facilities for MSMEs to issue and guarantee stocks and bonds by forming MSME holdings through the formation of clusters based on the type of industry. Investors will be interested in investing because MSME-based stocks and bonds are issued and guaranteed by the government, in this case through the Ministry of Cooperatives and Small and Medium Enterprises (SMEs). On the other hand, the government will get a multiplier effect by supporting MSME capital, given the large contribution of MSMEs to national economic growth. This study offers a model that can be used by the government in issuing and guaranteeing shares and bonds based on MSMEs with a sharia scheme